History of the Present Time and ethics: concerns about the sources (Tempo e Argumento, 2024)
Abstract: Based on the concerns raised by research and scientific publishing work in the field of the History of the present time, this article aims to discuss the difficult ethical boundaries that concern the access, use and presentation of historical sources. The text begins with an episode of conflict between different ethical dimensions raised by a judicial questioning to the practice of historiography. The situation proved to be complex in several ways, involving issues within the scope of the legislation constructed in Brazil since the 1990s around ​​research ethics. On the other hand, the text points to the developments of the so-called ethical-political turn and the possibilities of building paths, both methodological and epistemic, to address issues as broad as the autonomy of scientific research and the defense of human rights, with a view to writing a History of the present time that is as effective in its results as it is committed to ethical principles.
Keywords: history of the present time; sources; ethics; Brazilian legislation